Formação médica : relato de experiência de estudante PCD - Francisco, Caique Henrique (Universidade Federal de São Carlos, 2023)
This work describes the itinerary of a PCD student on the Medicine program at the Federal University of São Carlos during the period from 2018 and 2023. Its purpose is to present a personal perspective on the stages experienced within the scope of medical training. In this sense, the academic trajectory experienced is narrated in chronological order, describing the experiences of yet another young PCD student inserted in a unique pedagogical sphere that constitutes the medical course structured by the active PBL (Problem Based Learning) methodology, in the city of São Carlos, in the interior of São Paulo, Brazil. In the text, educational cycles are examined, which represent the milestones of demonstrating involvement. It is noteworthy that in this work the entire set of critical-reflective analysis expressed here takes place from the insurmountable perspective of a student with a physical disability during the pandemic of COVID-19 that ravaged the globe throughout most of the school periods. Finally, some paradigms of medical education are problematized in light of a universe of education — more than ever — dynamic, hyperconnected and, more recently, with innovative artificial intelligence and big data technologies at our disposal.
Medical education: a student with disabilities' experience report
Keywords: Metodologia ativa; PBL; PCD; Memorial crítico-reflexivo; Pandemia; Educação médica; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA